The phenomenon of Canavero - O. N. Reznik (Вестник трансплантологии и искусственных органов)
Modern medical technologies raise the problems of the relationship between man and society, medical workers and patients. The ethical problems of medical technologies are nowhere so clearly deﬁ ned as in the established practices of organ donation and transplantation. The project of a head transplant, widely represented in the media recently, raises a number of critical questions to the medical community. The article explores the ethical issues raised by the presentation in the media sphere the project of human head transplantation and risks for current transplant practice.